A hybrid SWOT analysis of the neuromodulation process for chronic pain. (2nd April 2020) - Puurunen, Anne; Ikäheimo, Tiina-Mari; Nissen, Mette; Huotarinen, Antti; Jyrkkänen, Henna-Kaisa; Huttunen, Jukka; Koivisto, Timo; von und zu Fraunberg, Mikael; Kajanus, Miika
Abstract : Background: Spinal cord stimulation is an efficient treatment for selected patients with chronic neuropathic pain. Since 2015, neuromodulation nurses at Kuopio University Hospital have been responsible for patient education and stimulator adjustments. Aims: The purpose is to determine what factors professionals perceived to affect patients' wellbeing in the neuromodulation process for chronic neuropathic pain. Methods: Four nurses and four physicians on the neuromodulation team performed a strengths, weaknesses, opportunities and threats analysis of the operational environment. All evaluated the attributes independently, and a multiple-criteria analysis was performed based on the results. Findings: The most important factors were excellent or good treatment results, having neuromodulation nurses, having a well-functioning neuromodulation team, vulnerability because of the limited number of specialists, and the establishment of a pain centre. Conclusion: This study highlights the importance of neuromodulation nurses and teamwork in chronic pain neuromodulation. The establishment of a multidisciplinary pain centre is strongly recommended.